Walking with lions: why there is no role for captive-origin lions Panthera leo in species restoration - Hunter, L; White, P; Henschel, P; Frank, L; Burton, C; Loveridge, A; Balme, G; Beritenmoser, C; Breitenmoser, U (2013)
Despite formidable challenges and few successes in reintroducing large cats from captivity to the wild, the release of captives has widespread support from the general public and local governments, and continues to occur ad hoc. Commercial so-called lion Panthera leo encounter operations in Africa exemplify the issue, in which the captive breeding of the lion is linked to claims of reintroduction and broader conservation outcomes. In this article we assess the capacity of such programmes to contribute to in situ lion conservation. By highlighting the availability of wild founders, the unsuitability of captive lions for release and the evidence-based success of wild-wild lion translocations, we show that captive-origin lions have no role in species restoration. We also argue that approaches to reintroduction exemplified by the lion encounter industry do not address the reasons for the decline of lions in situ, nor do they represent a model that can be widely applied to restoration of threatened felids elsewhere. Copyright © Fauna and Flora International 2012.